SYSTEM APPROACH AS A METHODOLOGICAL BASIS IN RESEARCH ON TEACHING BALLET ART - Maltsev, Anton; Rudachenko, Dmitriy; Rusinova, Svetlana; Miasnikov, Fatima (Revista Inclusiones, 2020)
The urgency of the problem under investigation is due to the fact that the generation of teachers who thoroughly master A.Ya. Vaganova’s methods of teaching is retiring due to their age. The young generation of classics teachers, in addition to the new requirements for the sociology of performances, should strictly follow the academic character of the Russian ballet; otherwise, irreparable losses will follow. The article is aimed at describing the didactic patterns of teaching classical ballet, listed in the system of the main aspects of this process. The article contains the results of the analysis, synthesis, and comparison that were the leading methods for applying the system approach as the methodological basis for the study. The ballet pedagogy has a centuries-old empirical experience, yet no generally recognized official status, the reason for this being the absence of teaching didactics. All the great ballet teachers were occupied with theoretical questions, yet this is not described as a studying theory, as a scientific justification of the existing laws, and is only by visual demonstration. The present study is the first to describe the learning process from the point of view of the ballet pedagogy didactics. A priori, the art of ballet is a system due to its specifics, and to the characteristics of ballet pedagogy, the term ‘system’ is also applied; however, the scientific substantiation of the processes of training ballet dancers (based on the principle of a systematic approach) was not conducted previously. The described results are sufficient to prove the application of this methodological approach. The materials of the article can be useful for the organization of reliable scientific research, since the methodology provides a correct and full implementation of the study of phenomena, processes, etc.